Studi Kejenuhan pada Current Transformer (CT) Akibat Arus Hubung Singkat - Giri Angga Setia; Een Taryana; Naufal Nur Aiman; Ahmad Daelami; Hikmah Prasetia (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
The CT saturation analysis approach model was carried out using ATPDraw and Mathcad software simulations. Input simulation data obtained from CT testing at West Priok Substation, namely ratio, excitation curve V-rms-Irms, Rct. Based on the simulation results, the CT model was successfully implemented for CT conditions at the West Priok Substation which experienced saturation, as seen from the results of the distorted waveforms and the THDi value of 40.612%. These results are then compared with the IEC 61869-2 standard with the parameters obtained from the CT-Analyzer test on E-t, Ek, Ie, Kx, and Rct, that E-t is -1%, Ek is 635.25 V, Ie is 13.5 mA, Kx of 0.084 and Rct of 7432.57 ohm. This result is a deviation from the specified standard, meaning that the CT is damaged and saturated. After replacing the CT, it was tested again and the value of E-t was -0.010%, Ek was 936.09 V, Ie was 9.68 mA, Kx was 14.39 A, Rct was 4.226 ohm, and the waveform simulation results were not distorted, then the THDi value obtained by 0.08%. This indicates that the CT is in good condition and does not experience saturation when the short circuit current is 20 kA.